2014
DOI: 10.1186/2052-336x-12-74
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arsenic (III, V) from aqueous solution by nanoscale zero-valent iron stabilized with starch and carboxymethyl cellulose

Abstract: In this work, synthetic nanoscale zerovalent iron (NZVI) stabilized with two polymers, Starch and Carboxymethyl cellulose (CMC) were examined and compared for their ability in removing As (III) and As (V) from aqueous solutions as the most promising iron nanoparticles form for arsenic removal.Batch operations were conducted with different process parameters such as contact time, nanoparticles concentration, initial arsenic concentration and pH.Results revealed that starch stabilized particles (S-nZVI) presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Polyvinyl alcohol (PVA) showed mechanical and chemical stability over other polymers and also possessed excellent adsorption capacity for the removal of toxic pollutants [50,65]. Ascorbic acid-coated Fe3O4 nanoparticles 16.56 mg/g pH = 7, 300 K, 60 mg/L adsorbent [60] Starch and Carboxymethyl cellulose (CMC) zerovalent iron 14 mg/g Adsorbent = 100-1000 mg/L, As = 2 mg/L, pH= 7 [61] Zero valent iron reduced graphene 29.04 mg/g 10 mg adsorbent, As(V) = 1-15 ppm, pH = 7.0 [62] Montmorillonite-supported nanoscale zero-valent iron 45.5 mg/g As = 5-250 mg/L, Adsorbent = 1 g/L, pH = 7 [63] Chitosan nanocompositesmagnetic nanoparticles 35.7 mg/g Adsorbent = 1 g/L, pH = 6.8 [24] Plant-synthesized IONPs chitosan hybrid 147 ± 7 mg/g As(V) = 300-8000 µg/L, Adsorbent = 25 g/L [64]…”
Section: Reuse Of Adsorbent and Iron Ion Releasementioning
confidence: 99%
“…Polyvinyl alcohol (PVA) showed mechanical and chemical stability over other polymers and also possessed excellent adsorption capacity for the removal of toxic pollutants [50,65]. Ascorbic acid-coated Fe3O4 nanoparticles 16.56 mg/g pH = 7, 300 K, 60 mg/L adsorbent [60] Starch and Carboxymethyl cellulose (CMC) zerovalent iron 14 mg/g Adsorbent = 100-1000 mg/L, As = 2 mg/L, pH= 7 [61] Zero valent iron reduced graphene 29.04 mg/g 10 mg adsorbent, As(V) = 1-15 ppm, pH = 7.0 [62] Montmorillonite-supported nanoscale zero-valent iron 45.5 mg/g As = 5-250 mg/L, Adsorbent = 1 g/L, pH = 7 [63] Chitosan nanocompositesmagnetic nanoparticles 35.7 mg/g Adsorbent = 1 g/L, pH = 6.8 [24] Plant-synthesized IONPs chitosan hybrid 147 ± 7 mg/g As(V) = 300-8000 µg/L, Adsorbent = 25 g/L [64]…”
Section: Reuse Of Adsorbent and Iron Ion Releasementioning
confidence: 99%
“…Very recently, synthetic nanoscale zerovalent iron (NZVI) stabilized with two polymers, Starch and Carboxymethyl cellulose (CMC) were investigated and compared for their capability in removing As (III) and As (V) from aqueous solutions as the most promising iron nanoparticles form for arsenic removal [79]. Furthermore, [80] studied the removal of copper (II) and lead(II) ions from aqueous solutions by Starch-graftacrylic acid/montmorillonite (S-g-AA/MMT) Nanocomposite.…”
Section: +mentioning
confidence: 99%
“…Starch stabilization was also found to enhance ZVI's ability for arsenic removal from aqueous solutions [38]. Kanel et al [39] also reported that polyoxyethylene sorbitan monolaurate-stabilized ZVI nanoparticles can effectively remove As(III) from water.…”
Section: Stabilized Zvi Nanoparticlesmentioning
confidence: 98%